Gender Mainstreaming Workshop: ReWater MENA Project & GENDER Project: COVID-19 and Egypt's Water Crisis - Generating Evidence for Gender-Transformative Innovations - International Water Management Institute; International Center for Agricultural Research in the Dry Areas; CGIAR GENDER Platform (International Water Management Institute, 2021)
This research project is conducted by IWMI and ICARDA, in collaboration with the Egyptian Agricultural Research Center and the Arab Water Council and supported by CGIAR GENDER Platform. It is built upon the preliminary findings of ReWater MENA project in Kafr El-Sheikh in Egypt, asking the question, “What are the gendered implications of COVID-19 on wastewater reuse agri-food value chains in Egypt?” Informed by a feminist political ecology approach, the project analyses how intersectional inequalities by gender, class and other social identities determine poverty, landlessness and [waste]water access, use and control. With this understanding, the project documents the nature and scale of challenges, including social and cultural barriers experienced by marginalized women as wastewater reuse irrigators, producers and entrepreneurs.